MATERNAL EDUCATIONAND FAMILYINCOME: IMPACTS ON MATHEMATIC PROFICIENCYLEVEL AS MEASURED BY SARESP - Bassetto, Camila Fernanda [UNESP]; Ursini, Driely Turi [UNESP]; Guedes, Alvaro Martim [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2023)
The present study consists of an analysis of the characteristics of the family environment and its relationship with school performance, using information collected by the School Performance Assessment System of the State of Sao Paulo (SARESP). The scores selected here are those obtained by students enrolled in the third year of high school in the state public school system of the state of Sao Paulo. The selected data are related to the discipline of Mathematics. The parental responses from the socioeconomic questionnaire applied by SARESP, referring to the 2019 edition, were also considered. The research observed the variables family income and maternal education level, to verify their impact on the student's performance. The organization of the data, associated with the analysis of the results obtained, allowed us to conclude that these family factors are limiting elements, such as family income in lower ranges, and drivers, revealed by the mother's higher levels of schooling, on educational performance, in addition to acting on the proficiency in Mathematics recorded in the aforementioned evaluation.
Keywords: Mathematics Performance; High school; Socioeconomic factors; Categorical variables; SARESP